Analisis Sentimen Publik Terhadap Peluang Timnas Indonesia Lolos ke Piala Dunia 2026 Dengan Algoritma Naïve Bayes dan Random Forest - Faizura Zadri (Jurnal Ilmu Komputer, 2025)
Football is a sport that is highly anticipated by the Indonesian people in 2025. This enthusiasm increases with the opportunity for the Indonesian national team to compete in the world's biggest football event, the 2026 World Cup which will be held in Canada, Mexico and the United States. There are various public opinions regarding Indonesia's chances of qualifying for the event, ranging from optimistic to pessimistic. This study was conducted to analyze public sentiment towards the chances of the Indonesian national team qualifying for the 2026 World Cup using the Naïve Bayes and Random Forest algorithms. The test results show that Naïve Bayes produces an accuracy of 79.6%, while Random Forest has the highest accuracy, which is 87.3%. Sentiment analysis using Random Forest shows that the majority of public sentiment is Neutral, which is 66.34%. This finding indicates that in general, the public is still doubtful or unsure about the chances of the Indonesian national team to qualify for the 2026 World.